MSMEs go digital: Marketing assistance for batik tulis products through e-commerce - Widyo, Nugroho Aris; Natasya, Ika Aurelia; Prasetyo, Satria Iman (Journal of Community Service and Empowerment, 2023)
The use of conventional marketing methods has a negative impact on the marketing of MSME Batik Tulis Mugissae products in Ngentakrejo Village. This is the background for Universitas Muhammadiyah Yogyakarta to carry out a community service program with the aim of assisting the marketing of digital based Batik Tulis MSME products. The mentoring implementation method is carried out in four stages, including: the stages of preparation, implementation, monitoring and evaluation and follow up plans. The results of the implementation provide assistance and education in strengthening understanding of digital based marketing. The preparatory stage is carried out through FGDs to produce a mature concept. The implementation phase is carried out by providing assistance in the form of product photos as MSME product branding, strengthening understanding of the use, marketing and promotion of Batik Tulis products through E-Commerce.